Maturity stages, Gonado-Somatic Index (GSI) and fecundity of leaping grey mullet, Liza saliens (Risso, 1810) in the western part of Iranian waters of the Caspian Sea (Guilan Province, Iran) - Davoud, Ghaninejad (2019)
The paper focuses on some of the biological characteristics of leaping grey mullet, Liza saliens (Risso,1810) in the western part of the Iranian waters of the Caspian Sea (off Guilan province). Samples of the mullet were taken monthly from commercial catch of beach seine fishing cooperatives (from October 2008 to April 2009). From May to September 2009 (a period not considered fishing season here), fish samples were obtained from local markets which caught them illegally. Fork length (FL), weight and sex were recorded for 302 fish. In addition, gonad weights were recorded for calculating Gonado-Somatic Index (GSI) and scales were removed for aging. The M:F (male/female) sex ratio of this species was 1:2.23 during the whole course of the study which deviate significantly from 1:1 common sex ratio (χ2=59.83, sig. level=0.000, df=1). During 2008-2009, the peak of the spawning time for leaping grey mullet occurred in July in Guilan shores. The highest GSI was found to occur during June-August and declined to its lowest level in September and remained relatively stable during October to April. The average absolute fecundity of leaping grey mullet was 207,050±134,630 (±SD) eggs with a range of 29,700 and 512,900 eggs. The length of females at 50% sexual maturity was estimated at 23 cm.